PERANAN DAN KEBUTUHAN PEMANGKU KEPENTINGAN DALAM TATA KELOLA PARIWISATA DI TAMAN NASIONAL BUNAKEN, SULAWESI UTARA - Heri Santoso; E.K.S Harini Muntasib; Hariadi Kartodihardjo; Rinekso Soekmadi (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2015)
Tourism management has been developed in Bunaken National Park (BNP) but has not shown satisfactory results. This research aim to identify and describe the roles and the needs of stakeholders in the governance of tourism in BNP. Data was collected through interviews, observation and document study, and then analyze by using the stakeholder analysis and requirements analysis. The results showed that there are 17 stakeholders, mostly serves as key players who have high interest and influence. Relationships among stakeholders are in the form of coordination, cooperation, and potential for conflict. The necessary requirements of the stakeholders, namely (1) the understanding of stakeholders on the BNP and its management, as well as the laws and regulations on governing the development of tourism in the conservation area, (2) coordination and communication at the regional level to unify the perception on the development of governance of tourism in BNP, and (3) implementation and synchronization of activities and programs of tourism development in BNP by stakeholders. Active roles and needs of the stakeholders can be met through more intensive coordination in supporting the management of BNP. The impact of the research is to provide input to the better tourism governance in BNP.